Mengasah Keterampilan Motorik Halus Dalam Kegiatan Menggunting Dan Menempel Pada Tk Al Maftuh Di Masa Pandemi Covid-19 - Yanti, Ai; Utami, Fitria Budi (Institut Agama Islam Negeri Ponorogo, 2021)
This research was conducted aimed at improving children's fine motor skills and increasing children's concentration power by cutting and sticking activities. The research was conducted at the Al-Maftuh Kindergarten unit, Sukamulya Village, Sukabumi. Where the researchers conducted research on 25 children of group B Al-Maftuh Kindergarten in Sukamulya Village. The research was conducted due to the lack of children's motor results in the previous year, so with this they would like to further improve their fine motor skills to be more thorough and neat in terms of writing, coloring, drawing with cutting and sticking activities where their fingers are trained as well as eye and eye coordination. careful hand.